Composite material for repairing heavy metal contaminated soil and preparation method thereof
By using a composite material composed of biochar and ZnFe2O4 to repair heavy metal contaminated soil, the problems of poor effect and difficulty in recycling of passivating agents in the prior art are solved, and effective passivation and environmentally friendly recycling of heavy metals in the soil are achieved.
Patent Information
- Application Number
- CN202411828365.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, when repairing heavy metal contaminated soil, the passivating agent is poor and difficult to recover, resulting in low pollution repair efficiency and high environmental risks.
A composite material composed of biochar and ZnFe2O4 is prepared by ultrasonic treatment, hydrothermal reaction and other methods to repair heavy metal contaminated soil. The composite material has excellent passivation effect, is low in cost and is easy to recycle.
After 30 days of addition, the content of total active states Tl, Cr, Pb, Ni and Cu in the contaminated soil was significantly reduced, with a decrease of 17~75%. At the same time, the magnetic properties of the composite material make it easy to recycle, reducing environmental risks.
Smart Images

Figure CN119709204A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental governance and relates to a composite material for repairing heavy metal contaminated soil and a preparation method thereof. Background Art
[0002] With the continuous development of mining, mineral processing, metallurgy, electroplating, chemical industry, dyes, metal processing and other industries, heavy metal pollution in soil caused by human factors has become increasingly serious, especially the development and smelting of non-ferrous heavy metal deposits is the main source of heavy metal pollution in soil. Since heavy metals cannot be decomposed by soil microorganisms, they have the characteristics of wide pollution range, long duration, difficult migration, hidden pollution and irreversibility. In addition, heavy metals in soil can enter the food chain after being absorbed by plants, gradually enrich in the human body, and endanger human health. Therefore, the remediation of heavy metal contaminated soil has attracted much attention.
[0003] Common remediation methods in the prior art can be divided into physical, biological and chemical remediation methods. Among the physical remediation methods, the soil-addition method is more commonly used, but this method is costly, and the removed soil also faces the problem of subsequent disposal. Among the biological remediation methods, microbial remediation and phytoremediation are more commonly used. Microbial remediation has the advantages of being environmentally friendly and low cost, but the microorganisms themselves are easy to variate, and the uncontrollability after addition makes microbial remediation difficult to carry out; phytoremediation is environmentally friendly, but hyperaccumulative plants are short, have low biomass, and require a long cycle, and mechanized operation is difficult, and harvesting is also prone to cause secondary pollution. Among the chemical remediation methods, passivation remediation is more commonly used. By adding a passivator to the heavy metal contaminated soil, the passivator and the heavy metal undergo physical and chemical reactions such as adsorption, precipitation / coprecipitation, complexation, ion exchange, and oxidation-reduction, thereby changing the occurrence form of heavy metals in the soil and reducing biological effectiveness, so as to achieve the purpose of repairing heavy metal contaminated soil.
[0004] However, existing passivators have the problem of poor passivation effect and difficulty in recycling. Therefore, it is of great significance to provide a composite material for repairing heavy metal pollution in soil, which has a better passivation effect and is easy to recycle. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a composite material for repairing heavy metal contaminated soil and a preparation method thereof. The composite material is composed of biochar and ZnFe2O4, has a better passivation effect when applied to heavy metal contaminated soil, and also has the advantages of low cost and easy recycling.
[0006] To achieve the technical purpose of the present invention, on the one hand, the present invention provides a method for preparing a composite material, using biochar and zinc ferrite as raw materials, mixing and ultrasonically treating for 30 minutes, adjusting the pH to 13, then hydrothermally reacting at 240°C for 24 hours, collecting the precipitate by centrifugation, rinsing with deionized water, and drying the precipitate at 60°C for 24 hours to obtain the composite material. Zinc ferrite is prepared by mixing C4H6O4Zn·2H2O and FeCl3·6H2O in water, and the mass ratio of biochar to zinc ferrite in the composite material is 3:4~4:3.
[0007] In another aspect, the present invention claims a composite material prepared by the above preparation method.
[0008] In addition, the present invention seeks to protect the use of the above-mentioned composite material in the restoration of heavy metal contaminated soil, the heavy metal contaminated soil including: Tl contaminated soil, Cr contaminated soil, Pb contaminated soil, Ni contaminated soil and Cu contaminated soil, and the addition amount of the composite material is 0.5-2% of the mass of the contaminated soil.
[0009] Furthermore, when the composite material is applied to the remediation of Tl contaminated soil, the mass ratio of the raw materials in the composite material is BC: ZnFe2O4 = 3: 4, and the dosage of the ZFBC composite material is 1% of the mass of the contaminated soil; or the mass ratio of the raw materials in the ZFBC composite material is BC: ZnFe2O4 = 4: 3, and the dosage of the ZFBC composite material is 2% of the mass of the contaminated soil. After the ZFBC composite material of the present invention is applied to the heavy metal contaminated soil for 30 days, the total active state content of Tl decreases by 17-35%.
[0010] Furthermore, when ZFBC composite materials are used for the remediation of Cr contaminated soil, the mass ratio of the raw materials in the ZFBC composite materials is BC:ZnFe2O4=3:4 or BC:ZnFe2O4=4:3, and the dosage of ZFBC composite materials is 0.5% of the mass of the contaminated soil. Under this condition, the reduction in the total active Cr content is 75.3% and 75.2%, respectively.
[0011] Furthermore, when ZFBC composite materials are used for the remediation of Pb-contaminated soil, the mass ratio of the raw materials in the ZFBC composite materials is BC:ZnFe2O4=5:4, and the dosage of ZFBC composite materials is 1% of the mass of the contaminated soil. Under this condition, the total active Pb content decreases by 54.7%.
[0012] Furthermore, when ZFBC composite materials are used for the remediation of Ni-contaminated soil and / or Cu-contaminated soil, the mass ratio of the raw materials in the ZFBC composite materials is BC:ZnFe2O4=3:4, and the dosage of ZFBC composite materials is 1% of the mass of the contaminated soil. Under this condition, the total active Ni and Cu contents decreased by 62.4% and 53.5%, respectively.
[0013] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages: The ZFBC composite material of the present invention is composed of biochar and ZnFe2O4, and has the advantages of low cost, environmental friendliness, easy magnetic recovery, etc., and also has a better effect of passivating metal pollution in the soil. After adding the ZFBC composite material to the tested contaminated soil, the total active Tl, Cr, Pb, Ni, and Cu contents in the contaminated soil are reduced to varying degrees compared with the blank control group.
[0014] It has a good passivation effect on Tl in contaminated soil. After 15 days of addition, the total active Tl content in the experimental groups with different ZFBC composite material raw material ratios decreased by 3-22% compared with the blank control group of 15 days. The best passivation effect on Tl contaminated soil was achieved when the addition ratio of BC:ZnFe2O4=3:4 was 1%, and the Tl content in F1 (weakly acid exchangeable state), F2 (reducible state) and F3 (oxidizable state) decreased by 31.8%, 21.2% and 21.1% respectively compared with the blank control group of 15 days. After 30 days of addition, compared with the blank control group of 30 days, the overall content of Tl in the total active state decreased by 17-35%, and the content of Tl in F1, F2 and F3 decreased by 7-60%, 7-30% and 20-35% respectively. The best passivation effect on Tl-contaminated soil was achieved when the addition ratio of BC:ZnFe2O4=4:3 was 2%, and the Tl content in F1, F2 and F3 decreased by 40.3%, 26.3% and 44.9%, respectively.
[0015] For other heavy metals (Cr, Pb, Ni and Cu) in contaminated soil, the passivation effect of ZFBC composite materials is also very significant, and it also mainly acts on reducing the content of F1 and F3. After passivation, the content of Cr, Pb, Ni and Cu in the weakly acid exchangeable state in the soil maintained a downward trend, decreasing to 0.274 mg / kg, 0.374 mg / kg, 0.590 mg / kg and 0.833 mg / kg respectively, with a decrease of more than 40% and a maximum of 80%. Cr, Pb, Ni and Cu in F3 are mainly combined with organic matter in the soil matrix, and the ability to form stable complexes is weak. They are released after being degraded by ZnFe2O4, resulting in the largest decrease in the content of this part, which can be reduced by more than 80%.
[0016] After 30 days of adding ZFBC composite materials, the total active Cr, Pb, Ni and Cu contents in the contaminated soil were reduced to varying degrees compared with the blank control group. When the addition amount of BC:ZnFe2O4=4:3 or 3:4 was 0.5%, the total active Cr content decreased the most, by 75.3% and 75.2%, respectively; when the addition amount of BC:ZnFe2O4=5:4 was 0.5%, the total active Pb content decreased the most, by 54.7%; when the addition amount of BC:ZnFe2O4=3:4 was 1%, the total active Ni and Cu contents decreased the most, by 62.4% and 53.5%, respectively.
[0017] The ZFBC composite material provided by the present invention has a better effect of fixing metal pollutants. Biochar itself can induce the generation of active oxygen (hydroxyl radicals, superoxide anion radicals and hydrogen peroxide, etc.), which can further promote the generation of strong oxidizing free radicals under the action of ZnFe2O4. The ZnFe2O4 loaded on the ZFBC composite material has a narrow band gap and can effectively absorb visible light. It can act as a photocatalyst. After the photochemical reaction occurs, H2O and OH on the catalyst surface - capture h + , generating hydroxyl radicals (·OH), while e - The dissolved oxygen adsorbed on the catalyst surface is captured to generate superoxide anion radicals (O2 - ), which can degrade organic matter and release oxidizable metal pollutants. Subsequently, these metal pollutants are transferred to the residual state through further complexation or precipitation of biochar, achieving a better passivation effect.
[0018] The addition of ZFBC composite material can increase the soil pH value. As the pH increases, Cr 6+ The adsorption capacity of Cr 6+ Reduced to less active Cr 3+ , while Cr 3+ It is retained in organic matter and soil minerals by combining with ligands. This adsorption-coupled reduction phenomenon will form less toxic and less soluble Cr 3+ Compounds, reducing environmental risks. Increased pH can also promote the 2+ The ZFBC composite material has the advantages of high porosity, rich functional groups (i.e., carboxyl and hydroxyl groups), high cation exchange capacity (CEC), etc. It can reduce the mobility of metal pollutants in contaminated soil through electrostatic attraction, surface complexation, precipitation and ion exchange. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some implementation cases of the present invention.
[0020] Figure 1 The following is a graph showing the content and form of heavy metals in the tested soil. F1 is the weakly acid exchangeable state, F2 is the reducible state, F3 is the oxidizable state, and F4 is the residual state.
[0021] Figure 2 This is a graph showing the effect of ZFBC composite materials on the content of active Tl in contaminated soil under different raw material ratios, different addition amounts and different addition times. Figure 2 a in the figure is the result of the effect of ZFBC composite materials on the content of active Tl in contaminated soil under different raw material ratios and different dosage conditions after 15 days of addition; Figure 2 b is the result diagram of the effect of ZFBC composite materials on the content of active Tl in contaminated soil under different raw material ratios and different addition amounts at 30 days after addition; A is the raw material mass ratio BC:ZnFe2O4=1:1; B is the raw material mass ratio BC:ZnFe2O4=3:4; C is the raw material mass ratio BC:ZnFe2O4=4:3; D is the raw material mass ratio BC:ZnFe2O4=4:5; E is the raw material mass ratio BC:ZnFe2O4=5:4; YT is the untreated original soil; KB is the soil without adding materials for 15 days or 30 days, which is the blank control group.
[0022] Figure 3 This is a graph showing the effect of ZFBC composite materials on the content of active Cr in contaminated soil under different raw material ratios, different addition amounts and different addition times. Figure 2 a in the figure is the result of the effect of ZFBC composite materials on the content of active Cr in contaminated soil under different raw material ratios and different dosage conditions at 15 days after addition; Figure 2 Figure b is the result of the effect of ZFBC composite materials on the content of active Cr in contaminated soil under different raw material ratios and different dosage conditions after 30 days of addition.
[0023] Figure 4 This is a graph showing the effect of ZFBC composite materials on the content of active Pb in contaminated soil under different raw material ratios, different dosages and different addition times. Figure 2 a in the figure is the result of the effect of ZFBC composite materials on the content of active Pb in contaminated soil under different raw material ratios and different dosage conditions at 15 days after addition; Figure 2 Figure b is the result of the effect of ZFBC composite materials on the content of active Pb in contaminated soil under different raw material ratios and different dosage conditions after 30 days of addition.
[0024] Figure 5 This is a graph showing the effect of ZFBC composite materials on the content of active Ni in contaminated soil under different raw material ratios, different dosages and different addition times. Figure 2 a in the figure is the result of the effect of ZFBC composite materials on the content of active Ni in contaminated soil under different raw material ratios and different dosage conditions at 15 days after addition; Figure 2 Figure b is the result of the effect of ZFBC composite materials on the content of active Ni in contaminated soil under different raw material ratios and different dosage conditions after 30 days of addition.
[0025] Figure 6 This is a graph showing the effect of ZFBC composite materials on the content of active Cu in contaminated soil under different raw material ratios, different dosages and different addition times. Figure 2 a in the figure is the result of the effect of ZFBC composite materials on the active Cu content in contaminated soil under different raw material ratios and different dosage conditions after 15 days of addition; Figure 2 Figure b is the result of the effect of ZFBC composite materials on the content of active Cu in contaminated soil under different raw material ratios and different dosage conditions after 30 days of addition. DETAILED DESCRIPTION
[0026] The technical scheme of the present invention is described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The experimental methods and detection methods described in each embodiment are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0027] Example 1 This embodiment provides a method for preparing zinc ferrite biochar (ZFBC), which specifically includes the following steps: Zinc ferrite biochar (ZFBC) was synthesized by microwave hydrothermal method. 2+ ):n(Fe 3+)=1:2 was mixed in 20mL deionized water, and the mass ratio of C4H6O4Zn·2H2O, FeCl3·6H2O and deionized water was 2.195:5.406:20 to obtain a mixed solution. Then, biochar (obtained from poplar wood chips sintered at 600℃) was added to the above mixed solution, and the mass ratio of biochar to zinc ferrite was 5:4, 4:5, 4:3, 3:4 and 1:1, respectively, followed by ultrasonic treatment for 30 min to completely disperse it in the solution. The pH value was adjusted to 13 with NaOH at a concentration of 6 mol / L, and then transferred to a high-pressure reactor, placed in an oven, and hydrothermally reacted at a reaction temperature of 240℃ for 24h. After the reaction solution was cooled to room temperature, the precipitate was collected by centrifugation and rinsed with deionized water. The obtained precipitate was dried in a drying oven at 60℃ for 24h. The obtained samples were ZnFe2O4 biochar composites with different proportions, ground into powder, and sieved through a 200-mesh sieve for later use.
[0028] Example 2 This embodiment provides the application of zinc ferrite biochar in soil remediation.
[0029] 1. Analysis of heavy metal content and form in the test soil The heavy metal content and form of the test soil (collected in the mining area of Southwest Guizhou) were analyzed. Figure 1 As shown in the figure, the contents of Tl, Cr, Pb, Ni and Cu in the tested soil were 110, 98.0, 55.8, 21.0 and 104 mg / kg, respectively, all exceeding the background values of the continental crust (0.45, 10, 15, 20 and 4 mg / kg), among which the enrichment of Tl was 240 times the background value of the continental crust. Compared with the background values of these five heavy metal elements in the soil of Guizhou Province (0.68, 99.0, 33.6, 39.3 and 34.5 mg / kg), except for Cr and Ni, all exceeded the local background values, among which Tl was the most seriously polluted, which was 160 times the local background value, and Cu was also as high as 3 times the local background value.
[0030] The chemical forms of the five heavy metals are not the same, but the residual state accounts for the largest proportion (59-90%). The active state content of heavy metals (F1+F2+F3) cannot be ignored. The total active state of Tl (10.4 mg / kg) is more than ten times the local background value. The most active weak acid exchangeable state (F1) has a content of 0.944 mg / kg, which also exceeds the local background value and the background value of the continental crust, and there is a health risk that cannot be ignored. Among the active states of Cr, the oxidizable state (F3) has the highest Cr content of 11.1 mg / kg, which exceeds the background value of the continental crust. The total active state content of Pb is 22.7 mg / kg, of which the reducible state (F2) has the highest content, reaching 17.0 mg / kg. The total active state content of Ni is 5.48 mg / kg, and the environmental risk is relatively low. The total active state content of Cu is 14.0 mg / kg, of which the reducible state (F2) has the highest content, reaching 7.52 mg / kg.
[0031] 2. Effects of ZFBC composite material raw material ratio, dosage and addition time on the passivation effect of Tl in contaminated soil There are five gradients in the mass ratio of ZFBC composite materials, namely A, BC: ZnFe2O4 = 1: 1; B, BC: ZnFe2O4 = 3: 4; C, BC: ZnFe2O4 = 4: 3; D, BC: ZnFe2O4 = 4: 5; E, BC: ZnFe2O4 = 5: 4. There are three gradients in the dosage, namely 0.5wt%, 1wt% and 2wt%; there are two gradients in the dosage time, namely 15 days and 30 days. The results of the effect of ZFBC composite materials on the content of active Tl in contaminated soil under different raw material mass ratios, different dosages and different dosage times are shown in the figure. Figure 2 shown.
[0032] Depend on Figure 2As can be seen from a in the figure, 15 days after the addition of the ZFBC composite material, the total active Tl in the contaminated soil (F1+F2+F3) was reduced to varying degrees compared with the 15-day blank control group (the content of Tl in the total active state was 9.63 mg / kg). When BC:ZnFe2O4=1:1, the passivation effect is best with a dosage of 1%, and the content of Tl in the total active state is 8.58 mg / kg; when BC:ZnFe2O4=3:4, the passivation effect is best with a dosage of 1%, and the content of Tl in the total active state is 7.51 mg / kg, and the decreases of F1, F2 and F3 are 31.8%, 21.2% and 21.1% respectively; when BC:ZnFe2O4=4:3, the passivation effect is best with a dosage of 2%, and the total active Tl content is 7.73 mg / kg); when BC:ZnFe2O4=4:5, the passivation effect is best with a dosage of 1%, and the total active Tl content is 8.01 mg / kg; when BC:ZnFe2O4=5:4, the passivation effect is best with a dosage of 2%, and the total active Tl content is 8.14 mg / kg. In summary, it can be seen that the ZFBC composite material with BC:ZnFe2O4=3:4 has the best passivation effect on Tl-contaminated soil when the addition time is 15 days.
[0033] Depend on Figure 2 As shown in b, after 30 days of adding ZFBC composite materials, the total active Tl content of the blank control group was 10.3 mg / kg, which was higher than that of 15 days. However, the addition of ZFBC can make more active Tl passivated and transferred to the residual state at 30 days, reducing its impact on the environment. When BC:ZnFe2O4=4:3, the passivation effect was best with a dosage of 2%, and the total active Tl content was reduced to 6.63 mg / kg. Compared with the blank control group, the Tl content in F1, F2 and F3 decreased by 40.3%, 26.3% and 44.9%, respectively. The part with a more obvious decrease in the content of active Tl was the oxidizable state (F3), and the ZFBC composite materials with BC:ZnFe2O4=3:4 and 4:3 had the best Tl fixation effect on this part.
[0034] After 15 days of adding ZFBC composite materials, the total active Tl content decreased by 3-22% compared with the blank control group after 15 days, among which the contents of weakly acid exchangeable state (F1), reducible state (F2) and oxidizable state (F3) decreased by 30-50%, 10-20% and 2-20%, respectively. After 30 days of addition, the content of Tl decreased by 17-35% compared with the blank control group after 30 days, among which the contents of Tl in F1, F2 and F3 decreased by 7-60%, 7-30% and 20-35%, respectively. Tl in F3 is mainly combined with organic matter and sulfide, and its ability to form stable complexes in the soil matrix is weak. The ZnFe2O4 loaded on the composite material has a narrow band gap and can effectively absorb visible light. It can act as a photocatalyst. After the photochemical reaction, H2O and OH on the catalyst surface - capture h + , generating hydroxyl radicals (OH·), and e - The dissolved oxygen adsorbed on the catalyst surface is captured to generate superoxide anion radicals (O2 - ). Biochar itself can induce the production of active oxygen (hydroxyl radicals, superoxide anion radicals and hydrogen peroxide, etc.), which can further promote the generation of strong oxidizing free radicals under the action of ZnFe2O4, degrade various organic matter, and release Tl in the oxidizable state. And because biochar has the characteristics of porous structure, large surface area and functional groups, it can effectively fix the released Tl.
[0035] At the same time, it can be observed that the weakly acid exchangeable state (F1) with the highest bioavailability in the active state has a certain degree of reduction. Among them, the ZFBC composite materials with BC:ZnFe2O4=3:4 and 4:3 have the best Tl fixation effect on this part. Compared with the blank control group, the reduction rate is 30~50% after 15 days of addition of ZFBC composite materials, and the reduction rate is 30~60% after 30 days of addition. The passivation effect is better than other reported biochar materials. Among them, the best passivation effect is the ZFBC composite material experimental group with a dosage of 2% and BC:ZnFe2O4=3:4. The F1 content in Tl decreased to 0.158 mg / kg (a decrease of 60%) after 30 days of addition.
[0036] The Tl in F1 is mainly Tl + It exists in the form of carbonate precipitation or retained in the soil by surface electrostatic adsorption of soil particles. In this state, Tl is easily changed with the change of pH. It is released again in a low pH environment and flows with the water in the soil, causing pollution in a wider range. Tl in F1 will be fixed by the abundant adsorption sites on the surface of the ZFBC composite material of the present invention, reducing its fluidity. At the same time, the iron oxide (ZnFe2O4) on the ZFBC composite material will also promote Tl+ Oxidized to Tl 3+ , and then adsorbed or precipitated onto the iron oxide particles.
[0037] 3. Effect of raw material ratio, dosage and addition time of ZFBC composite materials on the passivation effect of Cr in contaminated soil The raw material ratio, dosage and addition time of ZFBC composite material are the same as above. The results of the influence on the content of active Cr in contaminated soil are as follows: Figure 3 shown.
[0038] Depend on Figure 3 It can be seen from a that 15 days after the addition of ZFBC composite materials, it can be observed that the total active Cr content in the contaminated soil has increased to varying degrees compared with the blank control group (total active Cr content is 15.4 mg / kg). Among them, the fluctuation of the weakly acid exchangeable state (F1) and the oxidizable state (F3) is not obvious, and the main increase is the reducible state (F2), and it increases with the increase of the dosage. When the dosage of BC:ZnFe2O4=1:1, 3:4, 4:3, 4:5 and 5:4 is 2%, the Cr content in F2 reaches 8.21, 7.52, 8.50, 7.33 and 9.10 mg / kg respectively, compared with the blank control group F2 Cr content of 3.20 mg / kg, an increase of 2~3 times. The results show that the residual Cr in the contaminated soil is transferred by combining with iron and manganese oxides or hydroxides in the soil. Cr in the environment is generally Cr 3+ and Cr 6+ In the form of Cr 6+ It is soluble in the soil and can easily seep into groundwater or be absorbed by plants. 6+ It can be adsorbed on the surface of iron oxides, and it will also adsorb a certain amount of Cr ions on the surface of ZnFe2O4 particles in the ZFBC composite material, increasing the proportion of Cr ions combined with iron and manganese oxides in the repaired soil. 6+ In soil, it is not as mobile as in water, so Cr 6+ Unable to be fully released. 2+ and Cr 6+ Reaction occurs, generating a small amount of Fe 3+ , and then react with Cr adsorbed on negatively charged particles in the soil 3+ and unoxidized Fe 2+ Combined to form a stable ferrite, resulting in an increase in the content of the reducible state (the part combined with iron oxide), the reaction is as follows: Fe 2+ +Fe 3+ +Cr 3+ +OH - →Fe 2+ Fe3+ [Fe 1-x 3+ Cr 3+ O4]•xH2O Depend on Figure 3 As shown in b, 30 days after the addition of ZFBC composite materials, the total active Cr content in the contaminated soil decreased to varying degrees compared with the blank control group (total active Cr content was 15.3 mg / kg). The Cr content in the total active state of the composite materials of BC:ZnFe2O4=1:1, 3:4, 4:3, 4:5 and 5:4 reached the lowest when the addition amount was 0.5%, which were 4.37, 3.80, 3.78, 4.75 and 3.92 mg / kg respectively. The experimental groups with the smallest addition amount showed the best passivation effect, and the ZFBC composite materials with BC:ZnFe2O4=3:4 and 4:3 had the best passivation effect. The most obvious decrease in the active state was the oxidizable state (F3), which decreased to about 0.3 mg / kg.
[0039] The passivation behavior of Cr in soil is relatively complex, and there are changes in the valence state of Cr. 2+ and S 2- It is Cr 6+ Reduced Cr 3+ The main electron donor of Fe 2+ and S 2- It is easily oxidized, resulting in Fe 2+ and S 2- It is difficult to exist stably, so soil organic matter is considered to be Cr 6+ The composite material is loaded with zinc ferrite, a catalytic material with a spinel structure, which can produce hydroxyl radicals (·OH) and superoxide anion radicals (O2· - ) Such highly oxidizing free radicals can degrade organic matter in the soil to release Cr in the oxidizable state, and then transfer this part of Cr to the residual state through further complexation or precipitation of biochar, achieving a better passivation effect. Within 15 to 30 days after adding ZFBC composite materials, the Cr content in the weakly acid exchangeable state (F1) showed a steady downward trend, with a decrease of 30 to 50% compared with the untreated original soil, and the passivation effect was better than other reported biochar materials.
[0040] The application of ZFBC composite material can increase the soil pH value. The pH value is closely related to the valence state and mobility of Cr. As the pH increases, the Cr 6+ The adsorption amount of Cr is not only increased, but also more easily reduced to the less active Cr 3+ , while Cr 3+It is retained in organic matter and soil minerals by combining with ligands. This adsorption-coupled reduction phenomenon will form Cr with weak toxicity and insoluble 3+ compounds and reduce environmental risks.
[0041] 4. Effects of raw material ratio, dosage and addition time of ZFBC composite materials on the passivation effect of Pb in contaminated soil The raw material ratio, dosage and addition time of ZFBC composite material are the same as above. The results of the influence on the content of active Pb in contaminated soil are as follows: Figure 4 shown.
[0042] Depend on Figure 4 From a in the figure, it can be seen that 15 days after adding ZFBC composite material, it can be observed that the total active Pb content in the contaminated soil has a slight decrease compared with the blank control group (total active Pb content is 31.5 mg / kg). Except for BC:ZnFe2O4=4:3, the total active Pb content is the lowest at 1% addition, which is 24.9 mg / kg. The other raw material ratios all drop to the lowest value at 0.5% addition, which are: 27.3, 24.6, 25.2 and 24.9 mg / kg respectively. At the same time, it can be seen that the decrease in the content of oxidized Pb (F3) is the largest. Compared with the oxidized Pb content of the blank control group of 13.6 mg / kg, the minimum content of oxidized Pb when BC:ZnFe2O4=1:1, 3:4, 4:3, 4:5 and 5:4 is 3.30, 3.44, 3.42, 3.52 and 3.52 mg / kg, respectively, which is about 75% lower. The content of reducible Pb (F2) has increased slightly, indicating that after about 15 days of adding the composite material, the oxidized Pb mainly transfers to the reducible state and F4 (residual state).
[0043] Depend on Figure 4As shown in b, 30 days after the addition of ZFBC composite materials, the total active Pb content in the soil of the blank control group increased to 37.1 mg / kg, which was significantly higher than that of 15 days. The Pb content of F1, F2 and F3 increased by 0.639 to 0.720 mg / kg, 17.3 to 22.1 mg / kg and 13.6 to 14.3 mg / kg, respectively, and F2 had the largest increase. After 30 days of adding ZFBC composite materials, a good passivation effect appeared, except that the lowest active Pb content of BC: ZnFe2O4 = 4: 5 appeared at a dosage of 1%, which was 18.7 mg / kg. The lowest active Pb content of other proportions was 18.5, 17.6, 17.6 and 16.8 mg / kg at a dosage of 0.5%, respectively. Compared with the blank control group, the total active Pb decreased by about 50%. At the same time, the content of Pb in the weakly acid exchangeable state (F1) also decreased, and the lowest could reach 0.508 mg / kg, a decrease of 29.4% (BC:ZnFe2O4=4:3, dosage of 1%).
[0044] This is because ZFBC has the advantages of high porosity, rich functional groups (i.e., carboxyl and hydroxyl groups), and high cation exchange capacity (CEC). It can reduce the mobility of Pb in Pb-contaminated soil through electrostatic attraction, surface complexation, precipitation, and ion exchange. In addition, the application of ZFBC composite materials can increase the soil pH value and promote the removal of Pb. 2+ of the raw materials, and promoted the formation of precipitates such as Pb5(PO4)3Cl. Similar to the results after 15 days of addition, the most obvious decrease was in F3, with the maximum content of 1.89 mg / kg (BC:ZnFe2O4=3:4, dosage of 1%) and the minimum content of 0.357 mg / kg (BC:ZnFe2O4= 4:3, dosage of 2%). Compared with the F3 content of 13.3 mg / kg in the blank control group after 30 days, the contents decreased by 85% and 97%, respectively. Organic matter in the soil, such as humic acid, has rich complexing functional groups on its surface, which can form relatively stable complexes with Pb. Since the composite material is loaded with ZnFe2O4, it can promote the generation of hydroxyl radicals (·OH), superoxide anion radicals (O2· - ) Such highly oxidizing free radicals degrade the organic matter in the soil and release the Pb in the oxidizable state. This part of Pb is then transferred to the residual state through further complexation or precipitation of biochar, achieving a better passivation effect.
[0045] 5. Effect of raw material ratio, dosage and addition time of ZFBC composite materials on the passivation effect of Ni and Cu in contaminated soil The raw material ratio, dosage and addition time of ZFBC composite material are the same as above. The results of the influence on the content of active Ni and Cu in contaminated soil are as follows: Figure 5 and Figure 6 shown.
[0046] Depend on Figure 5 It can be seen from a that after 15 days of adding ZFBC composite materials, the total active Ni content in the contaminated soil increased to a certain extent compared with the blank control group (total active Ni content was 4.17 mg / kg). Except for BC:ZnFe2O4=3:4, which had the lowest total active Ni content (4.43 mg / kg) when the addition amount was 1%, the total active Ni content of other raw material ratios dropped to the lowest value under the condition of 0.5% addition amount, which were 4.36, 4.42, 5.29 and 4.39 mg / kg respectively. At the same time, it can be seen that the increase of reducible Ni (F2) was the largest. Compared with the reducible Ni content of the blank control group of 0.762 mg / kg, the highest content of reducible Ni when BC:ZnFe2O4=1:1, 3:4, 4:3, 4:5 and 5:4 were 2.83, 1.79, 3.36, 3.48 and 2.41 mg / kg respectively, which increased by 2 to 5 times. The increase in this part may be due to the NiO and Ni 2+ / Fe 3+ This is caused by the formation of oxides / hydroxides.
[0047] Depend on Figure 5 From b, we can see that after 30 days of adding ZFBC composite materials, the total active Ni content of the blank control group was 3.96 mg / kg, which decreased slightly. The addition of ZFBC composite materials also showed a good passivation effect at this time. When BC:ZnFe2O4=4:3 and 5:4, the total active Ni content reached the lowest value when the dosage was 0.5%, which was 1.99 and 1.61 mg / kg respectively; when BC:ZnFe2O4=1:1, 3:4 and 4:5, the total active Ni content reached the lowest value when the dosage was 1%, which was 1.60, 1.49 and 1.89 mg / kg respectively, with a decrease of about 50%. Among them, the decrease in oxidizable state (F3) Ni was the largest. When BC:ZnFe2O4=1:1, 3:4, 4:3, 4:5 and 5:4, the minimum contents of oxidized Ni were 0.112, 0.066, 0.061, 0.119 and 0.058 mg / kg, respectively. Compared with the oxidized Ni content of 2.31 mg / kg in the blank control group after 30 days, the decrease reached 90%, showing good passivation performance.
[0048] Depend on Figure 6From a in the figure, we can see that the content of total active Cu in the contaminated soil has increased to a certain extent compared with the blank control group (the content of total active Cu is 12.7 mg / kg). The main increase is in the reducible Cu (F2). Compared with the reducible Cu (5.84 mg / kg) in the blank control group, the content of reducible Cu increased by about 2 mg / kg after adding ZFBC composite materials, and the lowest values in different raw materials were 7.69, 7.56, 7.68, 7.53 and 7.61 mg / kg respectively. The content of oxidizable Cu (F3) decreased slightly, ranging from 0.5 to 0.9 mg / kg. This shows that ZFBC composite materials will promote the transfer of residual and oxidizable Cu to reducible Cu in the short term, increasing its environmental and ecological risks.
[0049] Depend on Figure 6 As shown in b, the total active Cu content in the blank control group was 13.6 mg / kg. Compared with the blank control group without ZFBC composite material 15 days later, the Cu content of F1 and F3 decreased, but the Cu content of F2 increased significantly, with an increase of 30%. After adding ZFBC composite material, the total active Cu in the contaminated soil decreased to a large extent, with a decrease of about 40%. The most obvious decrease was in the oxidizable state (F3) Cu. On the basis of 15 days, the content of this part showed a continuous downward trend, with the content as low as 0.2 mg / kg, a decrease of up to 95%.
[0050] The mechanism of reducing the oxidizable state (F3) of Tl, Pb and Cr in the composite material is similar to that in the composite material: because the composite material is loaded with ZnFe2O4, it can promote the generation of a series of highly oxidizing free radicals, degrading organic matter in the soil and releasing Ni and Cu in the oxidizable state. The composite material makes the contaminated soil have a higher cation exchange capacity, and the composite material has a rich pore structure, which is Cu 2+ and Ni 2+ Provides attachment points, a large number of carboxyl and phenolic hydroxyl groups on the surface of the material 2+ and Ni 2+ The formation of complexes reduces the content of mobile Ni and Cu in the soil and fixes them in the soil, thereby reducing the environmental risks of Ni and Cu.
[0051] The addition time of ZFBC composite material is within 15 to 30 days. With the increase of addition time, the content of Ni and Cu in the contaminated soil decreases to a certain extent, and it is related to the addition amount and the preparation ratio. When BC: ZnFe2O4 = 3: 4 and 4: 3, the reduction of Ni and Cu in F1 reaches the maximum, which can be reduced by 30% and 40% respectively. At the same time, by comparing the different addition amount groups of the same raw material ratio, it is found that the fixation effect of Ni and Cu in the contaminated soil in the weakly acid exchangeable state (F1) is the best when the addition amount is 2%, and the effect is relatively stable.
[0052] The embodiments described above are part of the embodiments of the present invention, but not all of them. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but only represents selected embodiments of the present invention. All other embodiments obtained without creative work and related deductions and substitutions made by ordinary technicians in the field under the conditions of the concept of the present invention belong to the scope of protection of the present invention.
Claims
1. A method for preparing a composite material, characterized in that: Biochar and zinc ferrite are used as raw materials, mixed and then ultrasonically treated for 30 minutes, the pH value is adjusted to 13, then a hydrothermal reaction is carried out, and the precipitate is collected and dried to obtain the composite material.
2. The method for preparing a composite material according to claim 1, characterized in that: Mixing C4H6O4Zn·2H2O and FeCl3·6H2O in water to prepare the zinc ferrite; The mass ratio of the biochar to zinc ferrite is 3:4 to 4:
3.
3. The method for preparing a composite material according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 240°C and the time is 24h; The drying temperature is 60° C. and the drying time is 24 hours.
4. A composite material, characterized in that: The composite material is prepared by the method for preparing the composite material according to any one of claims 1 to 3.
5. Use of the composite material according to claim 4 in remediating heavy metal contaminated soil, characterized in that: The heavy metal contaminated soil includes: Tl contaminated soil, Cr contaminated soil, Pb contaminated soil, Ni contaminated soil and Cu contaminated soil; The dosage of the composite material is 0.5-2% of the mass of the contaminated soil.
6. The use according to claim 5, characterized in that: When the composite material is used for remediation of Tl contaminated soil, the mass ratio of biochar to zinc ferrite in the composite material is 3:4, and the addition amount of the composite material is 1% of the mass of the contaminated soil.
7. The use according to claim 6, characterized in that: The mass ratio of biochar to zinc ferrite in the composite material is 4:3, and the dosage of the composite material is 2% of the mass of the contaminated soil.
8. The use according to claim 5, characterized in that: When the composite material is used for remediation of Cr-contaminated soil, the mass ratio of biochar to zinc ferrite in the composite material is 3:4 or 4:3, and the dosage of the composite material is 0.5% of the mass of the contaminated soil.
9. The use according to claim 5, characterized in that: When the composite material is used for repairing Pb-contaminated soil, the mass ratio of biochar to zinc ferrite in the composite material is 5:4, and the dosage of the composite material is 1% of the mass of the contaminated soil.
10. The use according to claim 5, characterized in that: When the composite material is used for remediation of Ni-contaminated soil and / or Cu-contaminated soil, the mass ratio of biochar to zinc ferrite in the composite material is 3:4, and the dosage of the composite material is 1% of the mass of the contaminated soil.
Citation Information
Patent Citations
Passivator used for in-situ repairing of polluted farmland soil and processing method
CN107876557A
Composite passivator for repairing heavy-metal combined polluted farmland soil and use method thereof
CN107936972A
Passivating agent used for remediation of soil with multi-metal combined pollution and application method thereof
CN110387240A
Porous biochar / zinc ferrite composite material as well as preparation method and application thereof
CN112387249A
Application of magnetic charcoal-based iron carbide material in heavy metal contaminated soil remediation
CN113926845A